Migration and Foreign Remittances in the Philippines - Burgess, Robert (IMF Working Papers; Working Paper ;, 2005)
International migration and large remittance flows have been prominent features of the Philippine economy for many decades. This paper describes the evolving pattern of migration and remittance flows and analyzes some of the channels through which remittances affect economic activity. The empirical evidence does not clearly support the purported short-term stabilizing effect on consumption of remittance flows. Furthermore, as in other countries, the longer term economic effect of such flows is ambiguous.